PENGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEDANG BERTUMBUH YANG BERBEDA: (PENGUJIAN AGENCY THEORY) - Dwi, Bestari (Jurnal Analisis Bisnis Ekonomi, 2008)
This study purposed to test capitalstructure theory that was the effects of capital structure to company variable in different growing company based on agency cost. The capial structure theory tested in this study was agency theory tests. The sample observations were 70 manufacuring companies listed in BEJ that were grouped as growth and non growth companies by usingscore of P/E Raio. This study was using time series data (from 2004 until 2006). The hypothesis in this sudy as built based on agency theories. The hypothesis test was done by regressing independent and dependent variables in growth and non growth companies. Analysis to test result was done by comparing significant value (sig.t) among the results in the analysis by 95% degree freedom, regression analysis was also seen fron coefficient and t values taht were negative or positive. It was because hypothesis proposed in this study were positively or negatively correlated. The result of study showed taht there were evidences of manufacturing companies funding pattern in Indoneisa followed agency hypothesis. The result of regression model showed that leverage negatively affected tobin's q in growth company, while leverage positively affected to tobi's q in growth company.